Change in influenza vaccine uptake among adults in the United States from May 2020 to October 2024. - Hannah Melchinger; Sameer M Belgaumi; Noureen Ahmed; Saad B Omer; Amyn A Malik (PLOS Global Public Health)
Influenza vaccines are essential against the spread of influenza virus. In the United States, the Centers for Disease Control and Prevention (CDC) recommends vaccination to all eligible individuals over 6 months of age; however, uptake remains suboptimal nationally. We do not fully understand the current nuances of influenza vaccine uptake, nor how it has been affected by the coronavirus disease 2019 (COVID-19) pandemic. From 2020-2024, we conducted two distinct, cross-sectional surveys assessing influenza vaccine uptake among US adults. A census-matched national sample was recruited by online survey company CloudResearch, and respondents were asked whether they had or planned to receive the influenza vaccine. Analyses were stratified by demographic and weighted according to age, sex, and race estimates from the American Community Survey (ACS) 2022. We found that overall uptake decreased, with significant declines among demographic groups usually associated with higher vaccine uptake. Compared to 2022, individuals who were older (11% decrease), male (13%), White (7%), non-Hispanic (5%), or more educated (16%) were significantly less likely to receive the influenza vaccine in 2024. Changes in attitudes and intentions towards vaccination during and since the COVID-19 pandemic have been associated with several factors, including changes in perceived risk and the rise of vaccine-related mis- and disinformation. Targeted behavioral interventions can be used to shift attitudes, intentions, and eventually, behaviors, towards health-seeking behaviors like vaccination. We must target these demographics with evidence-based behavioral interventions to improve uptake of influenza vaccination.